Rotavirus vaccination in Japan: Efficacy and safety of vaccines, changes in genotype, and surveillance efforts. Issue 7 (July 2021) - Tsugawa, Takeshi; Akane, Yusuke; Honjo, Saho; Kondo, Kenji; Kawasaki, Yukihiko
Abstract: In Japan, a monovalent rotavirus vaccine (RV1) and a pentavalent rotavirus vaccine (RV5) were launched as voluntary vaccinations in November 2011 and July 2012, respectively. Rotavirus (RV) vaccine coverage in Japan increased from 30.0% in 2012 to 78.4% in 2019. The number of RV gastroenteritis hospitalizations decreased after 2014 in Japan, and is expected to decrease further following the introduction of RV vaccines into the national immunization program in October 2020. The incidence rates of intussusception (IS) among children aged <1 year were 102.8 and 94.0 per 100, 000 person-years in the pre-vaccine (2007–2011) and post-vaccine (2012–September 2014) eras, respectively. IS incidence did not increase following RV vaccine introduction in Japan. The efficacy and safety of RV vaccination were both documented in Japan. To reduce the risk of IS following RV vaccination, it is important that children receive a first dose of RV vaccine at age <15 weeks, preferably at age 2 months. Some strains that have emerged since RV vaccine introduction, such as DS-1-like G1P[8], eG3, and G8P[8], have spread nationwide. These three emerging genotypes did not affect the severity of the RV infection. Continuous city-level surveillance, using analysis of all 11 RV genome segments, is necessary to elucidate the genetic characteristics of prevalent RV strains. These efforts would also clarify the influence of vaccination on genetic changes of RV strains and the emergence of new genotypes.